Vegetative Propagation of Hoya imperialis and Hoya coronaria by Stem Cutting and Micropropagation - Siti Madihah Mohd Don; Nur Maziyyah Abdul Hamid; Hussein Taha; Rahayu Sukmaria Sukri; Faizah Metali (Tropical Life Sciences Research, 2021)
Hoya imperialis (H. imperialis) and H. coronaria (Apocynaceae) are known to have ornamental value due to their beautiful flowers; however, the feasibility of propagating these plants have not been reported despite the wild populations in Brunei Darussalam being highly threatened due to habitat loss and overcollection. Thus, the present study aimed to conduct a preliminary study of the feasibility of two alternative propagation methods, stem cutting and micropropagation, as a potential approach for their ex situ conservation. Hoya stem cuttings were treated with either indole-3-butyric acid (IBA) or 1-naphthaleneacetic acid (NAA) (0–2000 mg/L), and then propagated onto a mixture of peat moss and perlite. For micropropagation, Hoya leaf explants were cultured onto Murashige and Skoog (MS) agar media that were supplemented with IBA and/or kinetin (KN) (0–10.0 mg/L). This present study shows that both Hoya species were successfully propagated by stem cutting even without hormone treatment. However, interestingly, in H. imperialis, when compared with control, the mean number of new leaves (6.3 ± 1.0) and the mean relative growth rate (RGR) based on stem diameter (0.004 ± 0.0007 cm cm?1 day?1) significantly increased when treated with 500 mg/L NAA and 2000 mg/L IBA, respectively. Meanwhile, in H. coronaria, significantly higher mean number of roots was achieved by treating with 1000 mg/L NAA (16.6 ± 1.4) or 2000 mg/L IBA (17.5 ± 2.7) compared with control. For micropropagation, callus induction was not promising and could only be observed at specific concentrations of both IBA and KN, with H. imperialis appearing to be more responsive towards these hormones in comparison to H. coronaria. The present study showed that stem cutting appeared more feasible in propagating both Hoya species.